Probing the Circumstellar Environment of the Highly Luminous Type IIn Supernova ASASSN-14il - Dukiya, Naveen; Gangopadhyay, Anjasha; Misra, Kuntal; Hosseinzadeh, Griffin; Bostroem, K. Azalee; Ailawadhi, Bhavya; Howell, D. Andrew; Valenti, Stefano; Arcavi, Iair; McCully, Curtis; Gupta, Archana (The Astrophysical journal, 2024)
We present long-term photometric and spectroscopic studies of circumstellar material (CSM)–ejecta interacting supernova (SN) ASASSN-14il in the galaxy PGC 3093694. The SN reaches a peak r -band magnitude of ∼−20.3 ± 0.2 mag, rivaling SN 2006tf and SN 2010jl. The multiband and the pseudo-bolometric lightcurves show a plateau lasting ∼50 days. Semi-analytical CSM interaction models can match the high luminosity and decline rates of the lightcurves but fail to faithfully represent the plateau region and the bumps in the lightcurves. The spectral evolution resembles a typical Type IIn SN dominated by CSM interaction, showing blue continuum and narrow Balmer lines. The lines are dominated by electron scattering at early epochs. The signatures of the underlying ejecta are visible as the broad component in the H α profile from as early as day 50, hinting at asymmetry in the CSM. A narrow component is persistent throughout the evolution. The SN shows remarkable photometric and spectroscopic similarity with SN 2015da. However, the different polarization in ASASSN-14il compared to SN 2015da suggests an alternative viewing angle. The late-time blueshift in the H α profile supports dust formation in the post-shock CSM or ejecta. The mass-loss rate of 2–7 M ⊙ yr −1 suggests a luminous blue variable progenitor in an eruptive phase for ASASSN-14il.